Synthesis and Characterization of CuO@PANI composite: A new prospective material for electrochemical sensing - Meskher, Hicham; Achi, Fethi; Belkhalfa, Hakim (Journal of Composites and Compounds, 2022)
Herein, one-step oxidation-chemical polymerization in situ to prepare a composite of copper oxide nanoparticles doped with polyaniline(CuO@PANI) was investigated in order to check the electrochemical properties.The influence of the synthetic approach, the doping effectiveness of copper oxide nanoparticles, as well as the structure of the as-synthesized composite, were all studied. The synthesized compositewas characterized by field emission SEM and XFR. The results showed favorable interaction between PANI and CuO NPs. The electron microscopy analysis of the composite indicates that CuO is well dispersed and agglomerated in the PANI matrix as can be seen clearly in X-ray fluorescence analysis. Moreover, X-ray assessment indicated that the amount of CuO NPs strengthens the crystallinity of PANI. Moreover, to investigate the electrochemical performance of CuO@PANI, the composite was drop-casted on a glassy carbon electrode surface and its electrocatalytic activity was examined via a potentiostate in presence of catechol. As a result, the electrical conductivity of the synthesized hybrid was found to be drastically increased (around 60 %) as compared to that of pure PANI at room temperaturedue to the formation of conducting path between CuO and PANI surface. Hence, through this work we highly recommend to use this hybrid for future electrochemical sensing applications.